PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA MELALUI KEPUASAN KERJA PADA PEGAWAI PUSKESMAS KECAMATAN BALAPULANG KABUPATEN TEGAL - M. Abdul Aziz (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2016)
The purpose of this study were 1) to describe the motivation, discipline, work environment, satisfaction and performance 2) to analyze the influence of motivation, discipline, work environment to the satisfaction 3) to analyze the influence of motivation, discipline, work environment on employee performance 4) for analyze the influence of satisfaction on the performance of employee 5) to analyze the influence of motivation, discipline, work environment to performance through employee satisfaction. Respondents in this study as many as 99 people. The respondents are the employees of clinic balapulang. This study uses Structural Equation Modeling (SEM) was run through AMOS 4.00 as a tool of analysis. The results of data analysis proves motivation, discipline, work environment, significantly influence satisfaction as evidenced from the value of standardized regression coefficients (beta) of 0.01, discipline on job satisfaction to get a value of 0.81 and work environment to job satisfaction of obtained a value of 0.29. motivation, discipline and work environment significantly influence the performance of employees as evidenced from the value of standardized regression coefficients (beta) leadership on teacher performance gain value of 0.20, discipline on employees performance gain value of 1,32 and work environment on employees performance gain value of 0.62. Satisfaction significantly influence the performance of employees. This is evidenced from the p-value is very small (<0.001). Motivation, discipline, and work environment significantly influence performance through employees satisfaction as evidenced from the results sanggat pvalue small (<0.001). Keywords: motivation, disipmline, work environment, satisfaction, performance.